PENGGUNAAN EKSTRAK DAUN JAMBU BIJI (Psidium guajava L.) SEBAGAI DESINFEKTAN PADA DAYA TETAS DAN LAMA PENETASAN TELUR IKAN MAS (Cyprinus carpio L.) - Irawati Mei Widiastuti; Desiana Trisnawati Desiana Trisnawati Tobigo; Wahyuni Wahyuni (AgriSains, 2015)
Purposed this research was to know the excellent concentration of Psidium guajava L. leaf extract which give the highest hatching rate and hatching time of goldfish (Cyprinus carpio L.). The result was hoped to become an information source means to production high quality of goldfish seeds. The research used Completely Randomized Design whit five replication. The treatments were extract leaf Psidium guajava L. concentration : A (without leaf extract), B (30 ppm of leaf extract), C (32 ppm of leaf extract), D (34 ppm of leaf extract), and E  (36 ppm of leaf extract). The measured parameter were hatching rate and hatching time. Data that was analized by ANOVA and BNJ. The using extract leaf Psidium guajava L. give very significant effect to hatching rate but didn’t give any influence toward the hatching time of goldfish. The highest hatching rate of goldfish was at treatment D (34 ppm) with hatching rate amount 76% with hatching time 48,42 o’clock. Key words : Goldfish, hatching rate, hatching time, leaf Psidium guajava L.